Analisis Putusan Mahkamah Konstitusi No. 85/Puu-Xx/2022 Tentang Badan Peradilan Khusus Pemilu Perspektif Maslahah Mursalah - Hani Nurul Syifa; Cholida Hanum (Constitutional Law and Siyasah Department, Sharia and Law Faculty, IAIN, 2024)
It should be noted that with the decision of the Constitutional Court No. 85/PUU-XX/2022, the dispute over the determination of the final stage of the election results will be heard, examined and decided by the Constitutional Court, which was previously temporary, but has become permanent because a special electoral judicial body will no longer be established. This creates a polemic that leads to ineffectiveness. So it is interesting to be studied from the aspect of Maslahah Mursalah regarding a policy that can benefit the community and weigh the good or evil. The research method used is normative legal research. The results of the study, namely the legal considerations of the judges in deciding Constitutional Court Decision No. 85 / PUU-XX / 2022 concerning the Special Election Judicial Body, are that the phrase